Energy Migration Upconversion in Manganese(II)‐Doped Nanoparticles. (11th September 2015) - Li, Xiyan; Liu, Xiaowang; Chevrier, Daniel M.; Qin, Xian; Xie, Xiaoji; Song, Shuyan; Zhang, Hongjie; Zhang, Peng; Liu, Xiaogang
Abstract: We report the synthesis and characterization of cubic NaGdF4 :Yb/Tm@NaGdF4 :Mn core–shell structures. By taking advantage of energy transfer through Yb→Tm→Gd→Mn in these core–shell nanoparticles, we have realized upconversion emission of Mn 2+ at room temperature in lanthanide tetrafluoride based host lattices. The upconverted Mn 2+ emission, enabled by trapping the excitation energy through a Gd 3+ lattice, was validated by the observation of a decreased lifetime from 941 to 532 μs in the emission of Gd 3+ at 310 nm ( 6 P7/2 → 8 S7/2 ). This multiphoton upconversion process can be further enhanced under pulsed laser excitation at high power densities. Both experimental and theoretical studies provide evidence for Mn 2+ doping in the lanthanide‐based host lattice arising from the formation of F − vacancies around Mn 2+ ions to maintain charge neutrality in the shell layer.